2016
DOI: 10.1177/2054358116675343
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Effects of Febuxostat Therapy on Adipokines and Markers of Kidney Fibrosis in Asymptomatic Hyperuricemic Patients With Diabetic Nephropathy

Abstract: Background:In observational studies, higher uric acid levels are associated with metabolic syndrome, diabetes, and kidney disease.Objective:The objective of this study is to examine whether reduction of plasma uric acid with febuxostat, a xanthine oxido reductase inhibitor, impacts adipose tissue oxidative stress, adipokines, and markers of systemic inflammation or kidney fibrosis.Design:This was a double-blinded randomized controlled trial.Setting:Academic university setting was used.Patients:Overweight or ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…The number of participants ranged from 40 [ 14 , 16 ] to 179 [ 18 ]. All trials reviewed [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ] enrolled hyperuricemic (uric acid ≥ 6 mg/dL) CKD patients. Baseline uric acid levels ranged from ~6.2 [ 14 ] to 10.5 mg/dL [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of participants ranged from 40 [ 14 , 16 ] to 179 [ 18 ]. All trials reviewed [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 ] enrolled hyperuricemic (uric acid ≥ 6 mg/dL) CKD patients. Baseline uric acid levels ranged from ~6.2 [ 14 ] to 10.5 mg/dL [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 27 ] enrolled individuals with moderate-to-severe (stage 4–5) CKD. The prevalence of diabetes was available in eight studies [ 13 , 14 , 17 , 22 , 24 , 25 , 26 , 27 ], ranging from 21.5% [ 17 ] to 100% [ 14 , 26 ]. The mean age of patients ranged from ~40 [ 16 ] to 72.2 years [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that unexpected high plasma XOR activities possibly associated with liver dysfunction and insulin resistance are found in some women with a relatively low level of uric acid in a general population. There have been some interventional investigations on the effects of XOR inhibitors, including allopurinol, febuxostat and topiroxostat, on adipokine levels in humans, but results showed that XOR inhibitors did not significantly change levels of adipokines. Possible interventions for adipokines, including adiponectin receptor agonists, FABP4 inhibitors and FGF21 analogs, have been postulated in metabolic and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%